The learning challenge : dealing with technology, innovation and change in learning and development - Paine, Nigel, 1952- (Philadelphia, PA : Kogan Page, 2014)
"The landscape of workplace learning is transforming. Organizations today understand that formal training is not always the best solution in the fast changing world of innovation and new technology. The rise of social and informal learning, gamification of training, dealing with big data and creating value within the supply chain are just some challenges L&D professionals face in their work today.The Learning Challenge helps practitioners make sense of the latest developments in this area and their impact on the learning function in their organization. With the help of case studies and interviews from a range of high profile practitioners, the author defines the role of the new learning leader and illuminates the practical implications for creating and implementing a learning strategy for the 21st century"--
Includes bibliographical references (pages175-179) and index.
Keywords: Organizational learning; Employees -- Training of; Organizational change; BUSINESS & ECONOMICS / Development / Business Development; BUSINESS & ECONOMICS / Training; BUSINESS & ECONOMICS / Human Resources & Personnel Management